If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(2x + -14) + 13 = 4x + -27 Reorder the terms: 8(-14 + 2x) + 13 = 4x + -27 (-14 * 8 + 2x * 8) + 13 = 4x + -27 (-112 + 16x) + 13 = 4x + -27 Reorder the terms: -112 + 13 + 16x = 4x + -27 Combine like terms: -112 + 13 = -99 -99 + 16x = 4x + -27 Reorder the terms: -99 + 16x = -27 + 4x Solving -99 + 16x = -27 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -99 + 16x + -4x = -27 + 4x + -4x Combine like terms: 16x + -4x = 12x -99 + 12x = -27 + 4x + -4x Combine like terms: 4x + -4x = 0 -99 + 12x = -27 + 0 -99 + 12x = -27 Add '99' to each side of the equation. -99 + 99 + 12x = -27 + 99 Combine like terms: -99 + 99 = 0 0 + 12x = -27 + 99 12x = -27 + 99 Combine like terms: -27 + 99 = 72 12x = 72 Divide each side by '12'. x = 6 Simplifying x = 6
| (x^2-10x+9)=0 | | 72=3.6x | | 10=w^2(w+2) | | (-14)+8-6-(-5)= | | 2400+6Q^2=12Q | | w^2+2w-10=0 | | (-14)+8-6-(5)= | | y=.5x+17 | | 40=1.2x-4.2 | | 20x^2+45= | | 5x+129=13x-7 | | -26a^2b+86ab-8ab^2= | | 5x^2+13xy+6y^2= | | -3x+1+4x=-8+21 | | 25-5x=5-9x | | 44x^2-y^2-16x-16y-52=0 | | 4(2x+5)-3(5x-2)=o | | 4(9-16)= | | 14x^2-y^2-16x-16y-52=0 | | 3t^2+2t-8= | | 6a-2(a-1)= | | -x+6x-9=-4 | | 3(2z-7)+2(-2+3)=9 | | (1+1)+1(2+19)= | | 0.82x+x=60 | | 12n^2+8n-7= | | -5x+9=21 | | 2m+7m+9m-5= | | 8x+6=8(x+9) | | 2x+14y+21z=111 | | 2y^2+27y+13= | | 2x+14y+21z=11 |